The Comparison Of Starting Current In Three-Phase Induction Using Direct And Autotransformer Using Matlab Simulation - Sabam Sitorus; Adi sastra P Tarigan; Beni Satria (Jurnal Scientia, 2024)
Starting an induction motor can lead to a substantial initial current surge, causing a voltage drop that may surpass permissible limits. This surge, known as starting current, is characterized by a sudden and high-value current that occurs during the operation of a transformer or motor. Therefore, it is imperative to implement a proper starting method for a 3-phase induction motor. This study focuses on a 10 hp or 7.5 kW induction motor and employs Matlab simulation to analyze the starting characteristics. The simulation results reveal that an increase in the source voltage correlates with a proportional rise in the starting current. Adjusting the source voltage entering the Autotrafo provides a means to regulate and reduce the magnitude of the starting current. In the case of direct starting, the simulation indicates a starting current of 108.5 A at a speed of 1476 rpm, contrasting with a normal current of 9.218 A at a speed of 1464 rpm. On the other hand, starting with the autotransformer method yields a starting current of 76.14 A at a speed of 1467 rpm, with a normal current of 9.078 A at a speed of 1424 rpm. This results in a notable difference in starting current of 32.36 A. Comparatively, direct starting generates the highest starting current, emphasizing the necessity to avoid this method to prevent rapid motor breakdown. The autotransformer method proves to be a more efficient alternative, showcasing a reduced starting current and providing a more reliable and sustainable approach to initiate the induction motor.